2010
DOI: 10.1016/j.canlet.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential tumor-targeting abilities of three single-domain antibody formats

Abstract: The large molecular size of antibody drugs is considered one major factor preventing them from becoming more efficient therapeutics. Variable regions of heavy chain antibodies (HCAbs), or single-domain antibodies (sdAbs), are ideal building blocks for smaller antibodies due to their molecular size and enhanced stability. In the search for better antibody formats for in vivo imaging and/or therapy of cancer, three types of sdAb-based molecules directed against epidermal growth factor receptor (EGFR) were constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 38 publications
4
66
0
Order By: Relevance
“…Yves Durocher of the NRC, Canada kindly provided the cell line (CHODG44-EG2-hFc/clone 1A7). 31 The cells were cultured in 250 mL baffled shaker flasks (VWR International, Radnor, PA) at 120 rpm in an incubator at 37 C with 10% CO 2 overlay. The cells were grown in BioGro-CHO serum-free medium (BioGro Technologies, Winnipeg, MB) supplemented with 0.5 g/L yeast extract (BD, Sparks, MD), 1 mM glutamine (Sigma, St. Louis, MO), and 4 mM GlutaMax I (Invitrogen, Grand Island, NY).…”
Section: Cell Preparationmentioning
confidence: 99%
“…Yves Durocher of the NRC, Canada kindly provided the cell line (CHODG44-EG2-hFc/clone 1A7). 31 The cells were cultured in 250 mL baffled shaker flasks (VWR International, Radnor, PA) at 120 rpm in an incubator at 37 C with 10% CO 2 overlay. The cells were grown in BioGro-CHO serum-free medium (BioGro Technologies, Winnipeg, MB) supplemented with 0.5 g/L yeast extract (BD, Sparks, MD), 1 mM glutamine (Sigma, St. Louis, MO), and 4 mM GlutaMax I (Invitrogen, Grand Island, NY).…”
Section: Cell Preparationmentioning
confidence: 99%
“…Another pentabody V2C-EG2 (108 kDa) was constructed and then was labeled with 64 Cu using 1,4,7,10-tetraazacyclododecane-N,N′,N″,N‴-tetraacetic acid (DOTA) as a chelating agent for microPET/CT imaging in mouse tumor models; the results showed that 64 Cu-DOTA-V2C-EG2 failed to target EGFR in xenografted mice, which suggest that EG2-V2C is not an efficient probe. 24 Among the abovementioned multimers, we have reason to believe that EG2-COMP is the most promising antibody in tumor imaging and possible tumor therapy.…”
Section: Biodistribution Studiesmentioning
confidence: 99%
“…Mutagenesis and recombination of CDR regions to improve the affinity and specificity of sdAb fragments have also been discussed Fanning and Horn 2011). Current studies are focused on the development of new cloning and expression strategies to produce humanised fragments, multivalent constructs and fusions of antibody fragments to other proteins (Saerens et al 2005;Vincke et al 2009;Bell et al 2010;Pollithy et al 2011). Selected articles are presented in Table 4.…”
Section: Production Of Sdab Fragments Using Recombinant Technologymentioning
confidence: 99%